An Updated Comparison of Current Impression Techniques Regarding Time, Comfort, Anxiety, and Preference: A Randomized Crossover Trial - Hakan Yılmaz; Fatma Aslı Konca; Merve Nur Aydın (Galenos Yayinevi, 2021)
Objective: To compare digital and conventional impressions in terms of impression time, and comfort, anxiety, and preference of the patients.Methods: Digital scans (Trios 3 Cart) and conventional impressions (irreversible hydrocolloid material, hand-mixed) were randomly performed on 39 patients by a single experienced operator at 14-21-day intervals (crossover design). The impression time, comfort score with the visual analog scale, anxiety level with the State-Trait Anxiety Inventory, and preference with a questionnaire, were recorded. The 2 techniques were compared with the independent t-test in terms of time, comfort, and anxiety. Patient-operator assessment and time-comfort relationship were analyzed using Pearson's correlation test.Results: No statistical difference was found between the 2 impression techniques in terms of time (P = .231). Both the operators' and patients' comfort scores showed that the digital technique was found to be more comfortable (P < .001). There was no statistical difference between the 2 techniques with regard to anxiety (P = .668). The patients' and operators' comfort scores showed a strong correlation (P < .001), but no correlation was found between comfort and time (P > .05).Conclusion: Digital scanning and conventional dental impression were similar in terms of impression time and anxiety of patients. However, patients were more satisfied with the digital technique, and preferred it.